The reconstruction of language: some drawbacks - Temp, Daniel (Sofia, 2025)
Does the fact that a language can be artificially constructed using logical calculus from the structures of natural language provide evidence that language can be entirety rewritten formally? Or rather: to what extent can natural language be rewritten appropriately and without to prejudice its meaning through systems of formal symbolization? Based on the free consideration of some intuitions from Wittgenstein’s late philosophy, this text points out some difficulties for those who think they can give an optimistic answer to these questions.